2017
DOI: 10.1038/labinvest.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in obesity: insights for translational applications

Abstract: Obesity is now a major public health problem worldwide. Lifestyle modification to reduce the characteristic excess body adiposity is important in the treatment of obesity, but effective therapeutic intervention is still needed to control what has become an obesity epidemic. Unfortunately, many anti-obesity drugs have been withdrawn from market due to adverse side effects. Bariatric surgery therefore remains the most effective therapy for severe cases, although such surgery is invasive and researchers continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 148 publications
(190 reference statements)
1
40
0
Order By: Relevance
“…When cultured in specific inducing medium, MSCs reveal its osteogenic, chondrogenic or adipogenic potential. Since MSCs were proved to be a major source of adipocyte, the adipogenesis of MSCs affects the development of obesity and metabolic syndrome in various ways, and therapies based on MSC aiming to treat obesity and its commodities are raising increasing concern (2). For instance, Lee CW et al developed several MSC-based therapies which reduced obesity and metabolic disorders on rodents (3).…”
Section: Introductionmentioning
confidence: 99%
“…When cultured in specific inducing medium, MSCs reveal its osteogenic, chondrogenic or adipogenic potential. Since MSCs were proved to be a major source of adipocyte, the adipogenesis of MSCs affects the development of obesity and metabolic syndrome in various ways, and therapies based on MSC aiming to treat obesity and its commodities are raising increasing concern (2). For instance, Lee CW et al developed several MSC-based therapies which reduced obesity and metabolic disorders on rodents (3).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell transplantation is an excellent platform to metabolic syndrome-associated disease therapy, including obesity and type 2 diabetes [ 131 , 132 ]. Recent preclinical and clinical studies have revealed that stem cell therapy had been applied successfully in diabetes mellitus individuals.…”
Section: Future Perspective For Cellular Therapiesmentioning
confidence: 99%
“…In this study, we used two human cell lines; human mesenchymal stem cells (hMSCs) and human colon adenocarcinoma cells (HT-29) to investigate the effect of FaDOH on lipid metabolism at the cellular level. hMSCs are relevant cells as they play a key role in obesity ( Matsushita and Dzau, 2017 ) and are able to generate new adipose tissue through adipogenic differentiation driven by PPARγ ( Cristancho and Lazar, 2011 ). hMSCs have also shown a potential role in the treatment of diabetes ( Moshtagh et al, 2013 ) and have shown to be involved in the progression of cancers ( Lopatina et al, 2016 ; Ridge et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%